Grammatical Errors of Analysis in Writing E-Mail Committed by Reservation Staff at PT. Destination Asia Bali 2015/2016 - Shuandari, Ratna (Jurnal Pendidikan Bahasa Inggris Indonesia, 2019)
This study aimed at (i) To analyze the compatibility of the emails written by the staffs of PT. Destination Asia Tour & Travel with the format of formal email, (2) to analyze the types of errors committed by the reservation staff at PT. Destination Asia Tour & Travel, (3) to find out the sources of errors committed by the reservation staff at PT. Destination Asia Tour & Travel. This study was designed as a descriptive qualitative study. The data were collected by using research instruments such as analytical error analysis rubric, interview and observation sheet. The collected data were analyzed descriptively. From the data analysis it was found that (i) most of the emails have been written formally, almost all of the staff violated the element of formal email regarding to the non-contraction use in the email; (ii) all of the staff committed 16 (19%) errors of omission, 12 (14%) errors of addition, 47 (55%) errors of malformation and 10 (12%) errors of disordering; and (iii) the errors made by the staffs are caused by some factors namely staff’s incomplete knowledge, absence of knowledge, forgetting, language interference, over generalization and false concept hypothesized. Based on the conclusion of this study, it was suggested to the travel agent to provide their staffs an intensive course especially to improve their competence in writing formal email.